2018
DOI: 10.1186/s12890-018-0612-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous sex hormones on lung function and symptom control in adolescents with asthma

Abstract: BackgroundAlthough pre-puberty asthma is more prevalent in males, after puberty through middle-age, asthma is more prevalent in females. The surge of sex hormones with puberty might explain this gender switch.MethodsTo examine the effects of sex hormones on lung function and symptoms with puberty, Tanner stage was assessed in 187 children 6–18 years of age (59% severe) enrolled in the NIH/NHLBI Severe Asthma Research Program (SARP). The effects of circulating sex hormones (n = 68; testosterone, dehydroepiandro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 35 publications
9
70
0
2
Order By: Relevance
“…We found that post-albuterol FEV 1 was strongly associated with low DHEA levels [15] and that DHEAS levels were twice as high in non-severe as in severe asthma. We also found that women with severe asthma had low levels of DHEAS compared with women with nonsevere asthma (58.1 vs 131.5 lg/dL, p \ 0.001).…”
Section: Background and Significance Regarding Androgens For Patientsmentioning
confidence: 64%
See 2 more Smart Citations
“…We found that post-albuterol FEV 1 was strongly associated with low DHEA levels [15] and that DHEAS levels were twice as high in non-severe as in severe asthma. We also found that women with severe asthma had low levels of DHEAS compared with women with nonsevere asthma (58.1 vs 131.5 lg/dL, p \ 0.001).…”
Section: Background and Significance Regarding Androgens For Patientsmentioning
confidence: 64%
“…These data also suggest a protective effect of androgens on lung function. Further, DHEAS levels were strongly associated with lung function in male children [15]. For the majority of women and younger boys, adrenalderived DHEAS is the predominant androgen: the effect of testosterone is smaller.…”
Section: Background and Significance Regarding Androgens For Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…Epidemiological studies in women have shown variations in lung function and asthma exacerbations throughout the menstrual cycle. Some women report worsening of symptoms in the periovulatory period, and with most complications occurring in the preor peri-menstrual period (Zein and Erzurum 2015;DeBoer et al 2018). Therefore, it is likely that asthmatic women exposed to high ozone levels during the follicular phase experience a worsening of symptoms versus asthmatic women exposed in the luteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the overwhelming evidence showing the influence of sex or obesity in the development of respiratory diseases in humans, the mechanisms by which these two factors interact to influence asthma is not well understood. To date, the vast majority of publications in this field are longitudinal or cross‐sectional studies of human populations . Some reports have shown that nearly 75 percent of emergency room visits for asthma have been among obese individuals, and several cross‐sectional studies have found an increase in the prevalence of asthma among obese patients .…”
Section: Introductionmentioning
confidence: 99%